MODEL ROOT CAUSE ANALYSIS SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD) DALAM PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada Dinas Tenaga Kerja Kabupaten Wonogiri) - Praharaningtyas, Dian; Achyani, Fatchan; Triyono, Triyono (ITB AAS Indonesia Surakarta, 2024)
Use of the Regional Government Information System (SIPD) as a form of regional government transparency in disclosing information to the public. How SIPD is implemented in regional financial management at the Wonogiri Regency Manpower Service is the focus of this research. The author uses qualitative research with the Root Cause Analysis model